Pancreatic Cancer and Platelets Crosstalk: A Potential Biomarker and Target - Mai, Shaoshan; Inkielewicz-Stepniak, Iwona (Frontiers in Cell and Developmental Biology, 2021)
Platelets have been recognized as key players in hemostasis, thrombosis and cancer. Preclinical and clinical researches evidenced that tumorigenesis and metastasis can be promoted by platelets through a wide variety of crosstalk between cancer cells and platelets. Pancreatic cancer is a devastating disease with high morbidity and mortality worldwide. Although the relationship between pancreatic cancer and platelets in clinical diagnosis is described, the interplay between pancreatic cancer and platelets, the underlying pathological mechanism and pathways remain a matter of intensive study. This review summaries recent researches in connections between platelets and pancreatic cancer. The existing data showed different underlying mechanisms were involved in their complex crosstalk. Typically, pancreatic tumor accelerate platelets aggregation which form thrombosis. Furthermore, extracellular vesicles released by platelets promote the communication in neoplastic microenvironment, and illustrate how these interactions drive disease progression. We also discuss the advantages of novel model organoids in pancreatic cancer research. A more in depth understanding of tumor and platelets crosstalk which based organoids and translational therapies may provide potential diagnostic and therapeutic strategies for pancreatic cancer progression.